OPTIMALISASI TEKNOLOGI DIGITAL DALAM PROMOSI WARISAN BUDAYA MENGGUNAKAN WIX - Sya'adah, Nurul Afni; Yusdiawati, Yayuk (UI Scholars Hub, 2026)
Cultural heritage in tangible and intangible forms preserves important values for society and therefore must be preserved. However, its non-renewable nature poses a threat of extinction, which will result in the loss of cultural identity. This situation can be resolved through the use of digital technology in the process of promoting cultural heritage so that it can be accessed by the public. This community service is carried out as an effort to promote cultural heritage through digital platforms. The participants of the activity are students of the Archaeology Program at the Universitas Jambi, class of 2025. The activity was carried out in stages: preparation, implementation, guidance, and evaluation. This activity resulted in an introduction to cultural heritage and alternative promotional efforts using digital technology through WIX for students who will graduate in the fields of archaeology and culture. This activity produced students who are able to create websites for promoting cultural heritage in the digital media WIX.